2018
DOI: 10.1111/ijfs.13913
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐life extension and quality improvement of a Portuguese traditional ready‐to‐eat meat product with vinegar

Abstract: Cabec ßa de xara is a traditional ready-to-eat meat product (RTEMP) from the Portuguese region of Alentejo. It is a moulded galantine made of low value pork pieces. The aim of this work was to test the addition of vinegar in reducing the spoilage microbiota, as well as controlling Listeria monocytogenes, in order to increase the shelf-life of cabec ßa de xara. Physicochemical (fatty acids and biogenic amines profiles), microbiological (mesophiles, psychrotrophic bacteria, enterobacteria, yeasts and L. monocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…A previous study on a Portuguese traditional ready-to-eat meat treated with vinegar showed that sensory acceptability was not diminished by vinegar. Despite the lack of any discernible differences, vinegar samples typically received better ratings for overall appreciation [93]. The lowest sensorial scores observed for the thymol-carvacrol combination showed that despite the relatively low concentration used, consumers reported poor acceptability for the new oregano-flavored hummus, and they preferred the traditional original taste.…”
Section: Sensorial Analysismentioning
confidence: 93%
“…A previous study on a Portuguese traditional ready-to-eat meat treated with vinegar showed that sensory acceptability was not diminished by vinegar. Despite the lack of any discernible differences, vinegar samples typically received better ratings for overall appreciation [93]. The lowest sensorial scores observed for the thymol-carvacrol combination showed that despite the relatively low concentration used, consumers reported poor acceptability for the new oregano-flavored hummus, and they preferred the traditional original taste.…”
Section: Sensorial Analysismentioning
confidence: 93%
“…Natural fruit vinegar is high quality, safe, and nutritious, with characteristic sensory, microbiological, and physicochemical properties. However, some researchers have found that the addition of apple vinegar could affect the sensory quality of the final meat product, especially in terms of its color and consistency characteristics [19,20]. Therefore, this study aimed to assess the impact of different concentrations of apple vinegar addition on the quality of cooked sausage, focusing on changes in the fatty acid profile, oxidative stability, physicochemical parameters, as well as microbiological and sensory qualities after production and during chilling storage.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that lipid and protein oxidative processes cause flavour, texture and colour deterioration in meat systems (Smaoui et al ., , ; Arcanjo et al ., ). Equally, it is well known that the growth of several pathogenic bacteria and oxidative reactions affect the shelf life and overall quality of meat (Blanco et al ., ; Laranjo et al ., ).…”
Section: Introductionmentioning
confidence: 99%